(untitled) (diségno, 2017)
The research presents an analysis of the tabernacle designed in Bologna by Giovanni Maria da Bitonto who, with Francesco Borromini, created the perspectival gallery for the Spada Palace in Rome. The tabernacle perspective works as a projective system which accelerates the natural perspective perception and modifies environmental and spatial features, of the built scenography. The construction technique is complex if applied to architectural space: Donato Bramante realized it, for the first time, in Milan, in the choir of Santa Maria at San Satiro. The spatial fruition of perspective, usually linked to central perspective or to psychological and perceptive phenomenon, became ‘real’. The projective principle is the one known as ‘relief-perspective’, or designed to be used as a scenography or temporary installation. The survey of the tabernacle, in the church of San Paolo Maggiore in Bologna, reveals a small illusory space and also introduces a true protagonist of solid perspective applications, Giovanni Maria Bitonti. The research presents a graphic study of the perspective concept housed in the National Archive of Bologna and an accurate reconstruction of the solid perspective, using the most advanced techniques of digital documentation. The drawing examined has a graphic scale, in Bolognese feet; the drawing is of the model representing real architecture, making it comparable with the drawing of Spada Gallery conserved in the Albertina Library in Vienna.